Prevalence and determinants of termination of pregnancy among reproductive-age women who had a short preceding birth interval in Sub-Saharan Africa: a multilevel analysis - Zegeye, Alebachew Ferede; Tamir, Tadesse Tarik; Mekonen, Enyew Getaneh; Techane, Masresha Asmare; Terefe, Bewuketu; Workneh, Belayneh Shetie (Frontiers in Global Women's Health, 2024)
BackgroundTermination of pregnancy is one of the biggest five causes of maternal mortality in countries with low and middle incomes. Although termination of pregnancy is hazardous, its prevalence and determinates are not well studied in developing countries. Therefore, this study aims to assess the prevalence and determinants of termination of pregnancy among reproductive-age women who had a short preceding birth interval in Sub-Saharan Africa.MethodsData from the most recent Demographic and Health Surveys, which covered 21 Sub-Saharan African countries from 2015 to 2022, were used for secondary data analysis. The study used a total of 283,785 women. Stata 14 was used to analyze the data. The determinants of termination of pregnancy were determined using a multilevel mixed-effects logistic regression model. Significant factors associated with termination of pregnancy were declared significant at p-values < 0.05. The result was interpreted using the confidence interval and adjusted odds ratio. The best-fit model was determined to be the one with the highest log likelihood ratio and the lowest deviance.ResultsIn Sub-Saharan Africa, one in ten women with short birth intervals experienced pregnancy termination. Individual factors, including the sex of the preceding birth (AOR = 1.21, 95% CI: 1.05, 1.40), maternal age (AOR = 1.57, 95% CI: 1.27, 1.95), pregnancy complications (AOR = 1.28, 95% CI: 1.09, 1.49), No ANC visits (AOR = 2.29, 95% CI: 1.26, 4.14), previous cesarean section delivery (AOR = 1.74, 95% CI: 1.32, 2.30), <6 months of breastfeeding (AOR = 1.56, 95% CI: 1.35, 1.81), traditional contraception usage (AOR = 1.67, 95% CI: 1.13, 2.46), poor wealth status (AOR = 1.50, 95% CI: 1.22, 1.85), and community-level factors such as urban residence (AOR = 1.31, 95% CI: 1.06, 1.62) had higher odds of pregnancy termination.ConclusionsThis study concludes that termination of pregnancy rates among women with short preceding birth interval is high. The study identified that both individual and community-level variables were determinants of termination of pregnancy. Therefore, the ministries of health in Sub-Saharan African countries should give attention to those women who underutilize antenatal care services and to women from urban areas while designing policies and strategies targeting reducing termination of pregnancy rates.